Introduction to Views of Connectivism Theory of Learning - Sa’adi Sa’adi (UIN Salatiga, 2010)
‘Traditional’ theories of learning as pratical dimensions of psychology majorly tend to focus their interest on humans’ inner factors that influence the process of learning such as intelligences, motivation, interest, attitude, concentration and aptitude. They never connect it with instruments and technological inventions such as multimedia, cyber celluler, internet, even social organization, cultural values, traditions etc., while these are very influential nowdays towards the progress and behaviors of human life. As such the application of connectivism theory of learning which connect those dimensions of life with learning activities, is now and then insparable from any effort to promote the quality of humans’ learning itself, including in teaching and learning languages. keywords; Connectivism; Learning; Theory And Technology